Molecular and Pyrolyzed Penta-Coordinated Catalysts for the Oxygen Reduction Reaction: A Short Opinion Review on Electronic Properties and Catalytic Activity - Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Elsevier B.V., 2023)
Hydrogen fuel cells are emerging as a sustainable technology for the storage and transformation of chemical energy into electricity. Major problems to the mass diffusion of this technology are related to the sluggish reaction occurring at the cathode where molecular oxygen is reduced to water during the oxygen reduction reaction. The discovery of efficient and durable catalysts based on nonprecious metals is the most important step to improve the mass diffusion of the fuel cell technology. Particularly, iron-based catalysts derived from either molecular penta-coordinated (MN5) or atomically dispersed pyrolyzed MN4+1-C active sites, where Fe metal atoms are coordinated to 5 N atoms, have proved to be more efficient than the tetra coordinated analogous. This short review explores the recent advances for penta-coordinated active sites, from molecular or pyrolyzed nature, to deliver a comparison and an opinion, focusing on electronic properties and how these could affect the reactivity indexes. © 2023 Elsevier B.V.